KINETIKA ADSORPSI KARBON AKTIF DALAM PENURUNAN KONSENTRASI LOGAM TEMBAGA (Cu) DAN TIMBAL (Pb) - Ulfa Meila Anggriani; Abu Hasan; Indah Purnamasari1 (KINETIKA, 2021)
Heavy metals cause environmental pollution and affect human health because they are toxic. Cu and Pb are heavy metals that are often found in environmental pollution. One of the methods to reduce Cu (II) and Pb (II) metal content is adsorption using activated carbon. The purpose of this study was to determine the ability of activated carbon to absorb Cu (II) and Pb (II) metals, as well as to calculate its kinetics and adsorption capacity. Activated carbon with a certain amount (1 g and 1.5 g) is added to 50 ml of Cu (II) and Pb (II) metal solution for a certain time (0 - 40 minutes). The results obtained after the adsorption process were analyzed using Atomic Absorption Spectrophotometry (AAS). From the results of AAS analysis, it was found that activated carbon with a mass of 1.5 grams and a contact time of adsorption for 40 minutes was the most effective in reducing the concentration of Cu (II) and Pb (II) metals. Cu (II) metal adsorption follows Freundlich adsorption isotherm model while Pb (II) metal follows Langmuir adsorption isotherm model. The adsorption kinetics pattern of Cu (II) and Pb (II) metals follows second order kinetic adsorptions